MODELING OF C02 CAPTURE BY AMINE SOLUTIONS IN A HOLLOW FIBER MEMBRANE CONTACTOR - GILASSI, SINA (2014)
The absorption of carbon dioxide (CO2) by different amine solutions was investigated using a hollow fiber membrane contactor (HFMC) in this work. A reliable model can simulate an experimental work in order to investigate the effect of various operating parameters on C02 removal. The existing models had been developed with some assumptions such as applicable for specific absorbents, diffusive and convective mass transfers were neglected which affected accuracy of the modeling results. In this study, a comprehensive mathematical model was developed to predict C02 removal performance. The continuity equation was comprised of convection and diffusion terms for the shell and tube sides, and only diffusion term was applied for the membrane in axial and radial directions. The mesh generation was carried out on the basis of Finite Element Method (FEM) and then all equations were numerically solved by COMSOL (version 4.1) software.